Climate-Smart Agriculture Prioritization Framework (CSA-PF) Report for Guyana. - Lizarazo, Miguel; Sandoval, Danny; Eitzinger, Anton; Lopera, Diana Carolina (Bioversity International and the International Center for Tropical Agriculture, 2021)
The CCAFS-CIAT CSA Prioritization Framework (CSA-PF) is a participatory and multi-criteria decision-making process, co-designed as a holistic tool to support information-based CSA investments. CSA-PF has the objective to help decision-makers identify best-bet CSA investment portfolios that achieve gains in national food and nutrition security, farmers’ resilience and adaptation capacity to climate change, and, where possible, reduce greenhouse gas (GHG) emissions in the food system. The framework is divided into four additive phases: 1) Initial assessment of CSA options; 2) Identification of top CSA options; 3) Calculation of costs Figure 1 CSA-Prioritization Framework methodology overview and benefits of top CSA options; and 4) Evaluation of opportunities and barriers to adoption of CSA options, to finally co-create the CSA investment portfolio(s). The CSA investment portfolios are context-specific selection of priority agricultural practices and technologies that seek to maximize investment yield, explore possible synergies and avoid trade-offs, minimize income risk, and address priorities of various agricultural stakeholders harmonizing socio-cultural, politicalinstitutional, environmental, economic, and educational considerations in the territory.